(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
After 26 years of confrontation, the uneasy issue of the administrative border between Chechnya and Ingushetia has been resolved, even if between street protests. In the judgment of 6 December 2018 the Russian Constitutional Court was asked to resolve a rather thorny issue, namely the legitimacy of the agreement, reached following 26 years of negotiations between the (internal) Republics of Ingushetia and Chechnya, that established the administrative border. The applicant, the Head of the Republic of Inguscetia, asked for confirmation of the legitimacy of the acts despite the decision of the Constitutional Court of Ingushetia.